Inovasi Siap Melayani Di Rumah (Si Mamah) di Dinas Kependudukan dan Pencatatan Sipil, Kabupaten Pasuruan - Febriani, Reni; Sasmito, Cahyo; Nadeak, Hendrison (Yayasan Lentera Avanya Nagari, 2024)
Public services emerged with various forms of innovation provided. The purpose of the innovation service is to provide a service through good service for the needs of the community as in service innovations in public administration. An innovation is a renewal of ideas that someone has in running, creating, and improving a product or service with a value or benefit economically and socially. Innovation is an idea, idea, object, and practice that is based and accepted as a new thing by a person or certain group to be applied or adopted. This research uses a qualitative approach. Data collection is done through interviews, observation, and documentation. Data analysis uses Miles and Huberman's interactive model consisting of data reduction, data presentation, and conclusions. The results of this study show that the innovation